1998
DOI: 10.1093/emboj/17.23.6924
|View full text |Cite
|
Sign up to set email alerts
|

The TOR nutrient signalling pathway phosphorylates NPR1 and inhibits turnover of the tryptophan permease

Abstract: The Saccharomyces cerevisiae targets of rapamycin, TOR1 and TOR2, signal activation of cell growth in response to nutrient availability. Loss of TOR or rapamycin treatment causes yeast cells to arrest growth in early G1 and to express several other physiological properties of starved (G0) cells. As part of this starvation response, high affinity amino acid permeases such as the tryptophan permease TAT2 are targeted to the vacuole and degraded. Here we show that the TOR signalling pathway phosphorylates the Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
347
0
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(375 citation statements)
references
References 45 publications
23
347
0
5
Order By: Relevance
“…The protein kinase Npr1 plays a major role in the sorting of these two classes of permeases. Npr1 is required for stabilization of Gap1 at the plasma membrane and induces the degradation of Tat2, possibly by regulating their ubiquitination (Schmidt et al 1998;Springael and Andre 1998;De Craene et al 2001;Helliwell et al 2001;Soetens et al 2001;Springael et al 2002). TORC1 activity, through control of the Tap42-Sit4 phosphatase complex, promotes the phosphorylation of Npr1 (Schmidt et al 1998;Jacinto et al 2001;Gander et al 2008).…”
Section: Rapamycin-sensitive Signalling Via Torc1mentioning
confidence: 99%
See 1 more Smart Citation
“…The protein kinase Npr1 plays a major role in the sorting of these two classes of permeases. Npr1 is required for stabilization of Gap1 at the plasma membrane and induces the degradation of Tat2, possibly by regulating their ubiquitination (Schmidt et al 1998;Springael and Andre 1998;De Craene et al 2001;Helliwell et al 2001;Soetens et al 2001;Springael et al 2002). TORC1 activity, through control of the Tap42-Sit4 phosphatase complex, promotes the phosphorylation of Npr1 (Schmidt et al 1998;Jacinto et al 2001;Gander et al 2008).…”
Section: Rapamycin-sensitive Signalling Via Torc1mentioning
confidence: 99%
“…Presumably, this phosphorylation inhibits Npr1 which would promote Tat2 stabilization and Gap1 degradation. Accordingly, it was found that rapamycin induces Tat2 targeting to the vacuole and that this process depends on Npr1 (Schmidt et al 1998;Beck et al 1999). For Gap1, it was initially reported that rapamycin-induced inhibition of TORC1 did not affect its sorting (Chen and Kaiser 2002).…”
Section: Rapamycin-sensitive Signalling Via Torc1mentioning
confidence: 99%
“…In S. cerevisiae, TOR signaling has been proposed to respond to metabolic signals originating from nitrogen and carbon sources (Schmidt et al, 1998;Beck and Hall, 1999;Kuruvilla et al, 2001;Crespo et al, 2002). Glutamine deprivation inhibits TORC1 .…”
Section: Arsenic Inhibits Torc1mentioning
confidence: 99%
“…This is based on the observation that tap42-11, a temperaturesensitive allele of TAP42, confers semidominant resistance to rapamycin at the permissive temperature of 25°C (Di Como and Arndt 1996; Duvel et al 2003). Indeed, in tap42-11 cells, the activation of the transcription factors Gcn4, Gln3, Gat1, and Msn2/4, and the kinase Npr1, normally observed after inhibition of TORC1 with rapamycin, is partially or, in some cases, completely blocked (Schmidt et al 1998;Cherkasova and Hinnebusch 2003;Duvel et al 2003;Santhanam et al 2004).…”
mentioning
confidence: 99%